A study of gender differences in compliments and responses of Chinese international students / Zhao Jian Xiang - Zhao, Jian Xiang (2013)
As a positive speech act, compliments and compliment responses play an important role as a polite speech act in activities of daily verbal communication. Incorporating the questionnaires survey and theories in pragmatics and sociolinguistic views of gender differences in language, this study investigated the gender differences in compliments and compliment responses. Twelve situations were set in the questionnaire to investigate the gender differences in compliments and compliment responses used by Chinese international male and female students in University of Malaya (UM). Among them, six situations are about compliments, and six situations are about compliment responses. The study was carried out through the use of questionnaire which was adapted from Lorenzo-Dus’ (2001). This study obtained 269 compliments and 360 compliment responses which were given by 60 Chinese international students (30 males and 30 females) who were selected from different faculties in University of Malaya (UM). The findings are as follows: (1) In terms of making compliments, Chinese international students tend to give compliment to others and females use more explicit compliments than males, while males use more implicit, non-compliment and no response strategy. (2) In terms of responding compliments from the others, Chinese international students prefer acceptance strategy to rejection strategy. Females use acceptance and combination strategy more than males, while males use more non-acceptance, acceptance with amendment, and no response strategy than females. Under the guidance of pragmatics and sociolinguistics, compliment and compliment response strategies are discussed in terms of Politeness Principle, Face Theory, and Sociolinguistic views of gender differences in language. It is concluded that the western culture influences Chinese international students’ employment of pragmatic strategies, which are mostly a compromise under the guidance by Universal Politeness Theories and Chinese socio-cultural context. The gender differences in compliments and compliment responses among Chinese international students not only reflect Chinese traditional culture and different roles males and females play in the societies, but also show the different viewpoints about the function of compliment behavior.